Parents’ Perception of Rehabilitation Services for their Children with Special Healthcare Needs in Helena Center in Erbil City - Zainab Abdulrahman Abdullah1 , Kareem Fatah Aziz2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objective: First, to determine the socio-demographic characteristics; second, to identify parents’ perception of rehabilitation services; and third, to find out the relationship between socio-demographic characteristics and parents’ perception of rehabilitation services. Methods: A descriptive cross sectional study was carried out. The data were collected from May 2019 to September 2019. A non-probability convenience sampling was used, and sample size of 335 parents who attending to Helena center for rehabilitation and operation children with special needs in Erbil city was calculated. Results: The majority (around 80% or more) of the parents had positive attitudes toward the rehabilitation services provided in the center. Conclusion: Parents of children with special health care needs in Helena Center perceived services provided to their children as family-centered.